Diagnosis of Biliary Duct Obstruction by Magnetic Resonance Imaging Cholangiography - Zahraa Sabah Abdel Zahra Muhammad; Mohammed Riyadh Saadi; Yasir Osamah Taha haydar; Abbas Lafta Abd Ali Hassan; Hussein Hakim Ahsoonee Makroud (Genius Journals, 2024)
Magnetic resonance cholangiopancreatography (MRCP) is a valuable method for the evaluation of Biliary Ducts obstruction and a valuable alternative to endoscopic retrograde cholangiopancreatography (ERCP). It is noninvasive and does not require the use of contrast material or ionizing. To evaluate the accuracy of magnetic resonance (MR) cholangiopancreatography in the diagnosis of Biliary Ducts Obstruction
Keywords: Biliary Duct Obstruction; Imaging Cholangiography